Computational Intelligence Methods for Bioinformatics and Biostatistics 9th International Meeting, CIBB 2012, Houston, TX, USA, July 12-14, 2012 Revised Selected Papers - Peterson, Leif E.; Masulli, Francesco; Russo, Giuseppe; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 9th International Meeting on Computational Intelligence Methods for Bioinformatics and Biostatistics, CIBB 2012, held in Houston, TX, USA during in July 2012. The 16 revised full papers presented were carefully reviewed and selected from 23 submissions. The papers are organized in topical sections on relativistic heavy ions and DNA damage; image segmentation; proteomics; RNA and DNA sequence analysis; RNA, DNA, and SNP microarrays; semi-supervised/unsupervised cluster analysis.
Relativistic heavy ions and DNA damage -- Image segmentation -- Proteomics -- RNA and DNA sequence analysis -- RNA, DNA, and SNP microarrays -- Semi-supervised/unsupervised cluster analysis.
Keywords: Computer science; Computer software; Data mining; Computer vision; Optical pattern recognition; Bioinformatics; Computer Science; Computational Biology/Bioinformatics.; Pattern Recognition; Data Mining and Knowledge Discovery; Computation by Abstract Devices; Image Processing and Computer Vision; Algorithm Analysis and Problem Complexity